Insular pathology in young people with high-functioning autism and first-episode psychosis. Issue 14 (24th April 2017) - Parellada, M.; Pina-Camacho, L.; Moreno, C.; Aleman, Y.; Krebs, M.-O.; Desco, M.; Merchán-Naranjo, J.; Del Rey-Mejías, A.; Boada, L.; Llorente, C.; Moreno, D.; Arango, C.; et al.
Abstract : Background: Autism Spectrum Disorders (ASD) and psychosis share deficits in social cognition. The insular region has been associated with awareness of self and reality, which may be basic for proper social interactions. Methods: Total and regional insular volume and thickness measurements were obtained from a sample of 30 children and adolescents with ASD, 29 with early onset first-episode psychosis (FEP), and 26 healthy controls (HC). Total, regional, and voxel-level volume and thickness measurements were compared between groups (with correction for multiple comparisons), and the relationship between these measurements and symptom severity was explored. Results: Compared with HC, a shared volume deficit was observed for the right (but not the left) anterior insula (ASD: p = 0.007, FEP: p = 0.032), and for the bilateral posterior insula: (left, ASD: p = 0.011, FEP: p = 0.033; right, ASD: p = 0.004, FEP: p = 0.028). A voxel-based morphometry (VBM) conjunction analysis showed that ASD and FEP patients shared a gray matter volume and thickness deficit in the left posterior insula. Within patients, right anterior ( r = −0.28, p = 0.041) and left posterior ( r = −0.29, p = 0.030) insular volumes negatively correlated with the severity of insight deficits, and left posterior insular volume negatively correlated with the severity of 'autistic-like' symptoms ( r = −0.30, p = 0.028). Conclusions: The shared reduced volume and thickness in the anterior and posterior regions of the insula in ASD and FEP provides the first tentative evidence that these conditions share structural pathology that may be linked to shared symptomatology.